Land Use Relationship to Fluctuations in The Number of Trans Jogja Passengers During The Covid-19 Pandemic - Amartya Rizki Ananda; Bambang Hari Wibisono (Journal of Civil Engineering and Planning (JCEP), 2023)
Transportation and land use have a retroactive reciprocal relationship. As an impact of the Covid-19 pandemic, there are changes in the intensity of acticities in certain districts. This ultimately has an impact on people’s mobility patterns, especially in terms of using public transportation, as proven by the drastic decrease in the number of assangers. This study aims to identify the relationship between land use and fluctuations in the number of Trans Jogja passengers during the Covid-19 pandemic. The analysis was conducted using a qualitative descriptive method. The findings of this study shows that the variation in fluctuations in the number of passegers that occur is a consequence of the variation in the characteristics of the area around the Trans Jogja corridor. Tourism distric with a high density of activities tend to be more sensitive to a certain conditions. The greater the impact received by a land use due to certain conditions, in this case the Covid-19 pandemic, the greater the influence on the public transportation corridor through it.